The management of elbow fractures in children - (:unkn) unknown (My University, 2004)
Pediatric elbow fractures can be challenging to manage. Compression of the medial column in Gartland Type I and Type II supracondylar fractures must be reduced to prevent varus deformity. Gartland Type III fractures may be stabilized with two lateral pins or a medial lateral cross-pin technique. Non-displaced lateral condyle fractures require vigilant follow-up. Open reduction of displaced lateral condyle fractures should avoid posterior dissection. T-condylar fractures in children rarely have the articular comminution found in adults. Monteggia fractures in children can be managed well if recognized and treated promptly. Restoration of the ulnar length often reduces the radial head. Angulated proximal radius fractures need to be reduced in order to restore the ability to supinate and pronate. It is important to recognize and understand the diagnostic features of each type of fracture in order to determine the best course of treatment.